Volatile emissions from past eruptions at La Soufrière de Guadeloupe (Lesser Antilles): insights into degassing processes and atmospheric impacts - Metcalfe, Abigail; Moune, Séverine; Moretti, Roberto; Komorowski, Jean-Christophe; Aubry, Thomas J. (Frontiers in Earth Science, 2023)
Volatiles exert a critical control on volcanic eruption style and in turn impact the near source environment and global climate. La Soufrière de Guadeloupe in the Lesser Antilles has been experiencing volcanic unrest since 1992, increasing to a peak in 2018. The lack of data available on volatiles from past eruptions, and the well-developed hydrothermal system makes understanding deep-released volatile behaviour challenging. In this study, we analyse new melt inclusions and shed light on the volatile lifecycle and impacts at La Soufrière de Guadeloupe. We focus on four eruptions: 1657 CE (Vulcanian), 1010 CE (Plinian), 341 CE (Strombolian) and 5680 BCE (Plinian), and compare to the well-studied 1530 CE (Sub-Plinian) eruption. The maximum volatile content of these eruption melt inclusions are: 4.42 wt% H2O, 1700 CO2 ppm, 780 ppm S, 0.36 wt% Cl and 680 ppm F. We observe a decrease in S content over time indicating the whole system is evolving by early separation of FeS, resulting in a lower S content in younger magma. Using the CHOSETTO v1 model, we modelled degassing paths related to decompression at low pressures, suggesting the majority of S degassing has occurred during magma ascent. We also calculate the SO2 emissions using the petrologic method, and while the 1657 CE, 1530 CE and 341 CE eruptions have negligible emissions (0.0001–0.001 Mt of SO2), the 1010 CE and 5680 BCE eruptions (0.2 Mt and 0.3 Mt of SO2, respectively) are greater. Using the SO2 emissions and plume height, we calculated the climate forcing associated with each event. The 1010 CE and 5680 BCE Plinian eruptions produced a peak global mean stratospheric aerosol optical depth (SAOD) of 0.0055 and 0.0062, respectively. This suggests, that even the largest eruptions of La Soufrière de Guadeloupe did not exert a significant climate forcing individually, but are important contributors to the volcanic stratospheric sulfate aerosol background resulting from relatively moderate but frequent explosive eruptions. Overall, this study provides new insights into degassing processes and climate forcing not only at La Soufrière de Guadeloupe, but also for other basaltic-andesitic, magmatic-hydrothermal systems. These new constraints are vital particularly if the volcano is currently in a state of unrest and will contribute to improving monitoring crisis management and long-term planning.